Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Species-specific bioaccumulation and biotransformation of antibiotics shape differential toxicological effects in a multi-level aquatic community - Bin Wang; Hailing Zhou; Mengting Li; Bingyu Shen; Lidan Zhang; Jiayi Yang; Yushi Fang; You Zi; Jinmei Chen; Yujie He; Rong Ji (Journal of Hazardous Materials, 2026)

Protein amyloid-like fibrils derived from cereals: Formation, structural characteristics, and applications - Boruo Yang; Haoju Zhao; Zihang Fu; Liting Shen; Liyuan Rong; Jianhua Xie (Food Research International, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Biotechnological upcycling of Laminaria japonica processing waste via Lactiplantibacillus plantarum fermentation: release and formation of antioxidant and tyrosinase-inhibitory compounds - Jing Wu; Haojie Lin; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Wuyin Weng; Shen Yang (Food Chemistry, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Crystal-facet regulation of SnO₂ {221} and {110} for selective detection of dimethyl carbonate and H2 gases in battery thermal runaway - Xun Shen; Aijun Yang; Ruochen Ding; Kehan Bo; Jifeng Chu; Pengxu Chen; Chenhui Li; Hongye Yuan; Huan Yuan; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

The evolutionary history of the Methyltransf_FA domain and its role in JH signal in silkworm, Bombyx mori - Chunyang Wang; Yang Yu; Qi Shen; Rong Xiong; Meiwei Guo; Jiamei Zhao; Dongsheng Yan; Rongcheng Zhang; Ping Chen (Insect Biochemistry and Molecular Biology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Assessment of Bacillus cereus spoilage potential and the antibacterial mechanism of Larimichthys crocea-derived peptide SDH73 against Bacillus cereus - Jing Wu; Guanglei Wei; Ritian Jin; Rong Lin; Wuyin Weng; Duo Liang; Xujian Qiu; Shen Yang (International Journal of Food Microbiology, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Microplastics impair wound healing via NAT10-mediated epigenetic dysregulation of FASN-PI3K/AKT signaling - Feng-Jie Shen; Wei-Nan Cao; Xue-Chun Han; Qiu-Yue Pan; Yuan Wang; Rong Zhang; Gang Wei; Jin-Kui Yang (NanoImpact, 2025)

Insights into immune and oxidative stress in rural homemakers exposed to VOCs during typical solid fuel utilization activities - Rong Feng; Hongmei Xu; Liyan Liu; Jieting Zhou; Hongai Zhang; Zhenxing Shen; Mengyun Yang; Jian Sun; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effect of myosin-kappa carrageenan pickering emulsions on the quality of bighead carp surimi gels - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2025)

Regulating crystal face of SnO2 films for selective detection of H2 and DMC - Xun Shen; Jifeng Chu; Jianbin Pan; Aijun Yang; Jinyi Wang; Kehan Bo; Huan Yuan; Yichen Liu; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2025)

The reutilization of oolong tea waste: Synthesis of carbon dots and antibacterial mechanism against Staphylococcus aureus - Weian Ye; Shen Yang; Ritian Jin; Duo Liang; Zhongyang Ren; Rong Lin (Food Bioscience, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

BCP4: A novel antimicrobial peptide with potent efficacy against Bacillus cereus in rice porridge - Weihong Tao; Wenjie Li; Ritian Jin; Duo Liang; Wuyin Weng; Rong Lin; Shen Yang (International Journal of Food Microbiology, 2025)

Enhancing the photo-induced oxidase-like activity of fluorescein with methyl viologen for colorimetric detection of organophosphorus pesticide - Yang Yin; Caiyun Yuan; Xinyu Wang; Dongjun Shen; Yu Rong; Jijun Liu; Yijuan Long; Huzhi Zheng (Food Chemistry, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Bacillus subtilis fermented shrimp waste isolated peptide, PVQ9, and its antimicrobial mechanism on four Gram-positive foodborne bacteria - Weihong Tao; Wenjie Li; Jude Juventus Aweya; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Shen Yang (Food Microbiology, 2025)

Sunflower-inspired smart evaporator with omnidirectional solar tracking for highly enhanced energy-capturing and sustainable freshwater harvesting - Yuchun Shen; Rong Zhang; Guodong Hou; Yu Chen; Peng Yang; Xiaoshi Qian; Shaochun Tang (Chemical Engineering Journal, 2025)

Prevalence and genetic characterization of linezolid resistance gene reservoirs in hospital sewage from Zhejiang Province, China - Weiyi Shen; Yanyan Hu; Dejun Liu; Yang Wang; Stefan Schwarz; Rong Zhang; Jiachang Cai (Science of The Total Environment, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Novel Pickering emulsions using polysaccharide-myosin complexes: Effect of polysaccharide types - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

High-resolution ocean color reconstruction and analysis focusing on Kd490 via machine learning model integration of MODIS and Sentinel-2 (MSI) - Yulin Yang; Ziyao Wang; Peng Chen; Xue Shen; Wei Kong; Genghua Huang; Rong Shu (Frontiers in Marine Science, 2024)
Oceanic water quality monitoring is essential for environmental protection, resource management, and ecosystem vitality. Optical remote sensing from space plays a pivotal role in global surveillance of oceanic water quality. However, the spatial resolution of current ocean color data products falls short of scrutinizing intricate small-scale marine features. This study introduces a hybrid model that fuses MODIS (Moderate Resolution lmaging Spectroradiometer) ocean color products with Sentinel-2 ‘s remote sensing reflectance data to generate high-resolution ocean color imagery, specifically investigating the diffuse attenuation coefficient at a wavelength of 490 nm (Kd490). To address the intricacies of coastal environments, we propose two complementary strategies to improve the accuracy of inversion. The first strategy leverages MODIS ocean color products alongside a geographic segmentation model to perform distinct inversions for separate marine zones, enhancing spatial resolution and specificity in coastal regions. The second strategy bolsters model interpretability during training by integrating predictions from conventional physical models into a Random Forest-based Regression Ensemble (RFRE) model. This study focuses on the coastal regions surrounding the Beibu Gulf, near Hainan Island in China. Our findings exhibit a strong concordance with MODIS products, achieving a monthly average coefficient of determination (R²) of 0.90, peaking at 0.97, and sustaining a monthly average root-mean-square error (RMSE) of less than 0.02. These results substantiate the model’s efficacy. Moreover, the annual trend analysis and localized assessment of the reconstructed Kd490 offer nuanced insights that surpass MODIS data, establishing a robust foundation for high-resolution water quality monitoring in coastal zones.

Benzo-12-crown-4 and β-diketone bi-functionalized ionic liquids for highly selective lithium extraction from alkaline solution - Shen Wang; Meng Rong; Lin-Bing Sun; Yunze Zhao; Huifang Xing; Liangrong Yang (Chemical Engineering Journal, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

Human milk oligosaccharide 2′-fucosyllactose alleviates DSS-induced ulcerative colitis via improving intestinal barrier function and regulating gut microbiota - Xianxiang Chen; Jiaruo Hu; Jun Yang; Qiang Yu; Yi Chen; Mingyue Shen; Liyuan Rong; Jianhua Xie (Food Bioscience, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

CLLU1 as an emerging biomarker in chronic lymphoid leukemia - Chunmeng Rong; Chenhao Liang; Jinze Shen; Yuhua Zhang; Qurui Wang; Fang Yang; Yalu Chen; Yuqing Luo; Meier Gu; Panpan Gao; Yongming Xia; Shiwei Duan (Human Cell, 2024)

Association between short-term exposure to ambient air pollution and upper respiratory tract infection in Kunshan - Hua Wang; Guohua Qian; Jian Shi; Wenjie Lu; Yingchao Chen; Kun Fang; Yang Shen; Huan Rong; Xuanhua Huangfu; Yan Feng; Wei Zhang; Kexun Zhang (International Journal of Biometeorology, 2024)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

OsTKPR1 proteins with a single amino acid substitution fail the synthesis of a specific sporopollenin precursor and cause abnormal exine and pollen development in rice - Feng Liu; Huiting Yang; Rong Tang; Wang Wang; Haodong Shen; Mengxue Xu; Tiancheng Hao; Yuanyuan Hu; Yunhui Zhang; Yiqun Bao (Plant Science, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Effect of peach trichome removal on post-harvest brown rot and on the fruit surface microbiome - Youming Shen; Xinna Li; Rong Xiong; Yang Ni; Shiping Tian; Boqiang Li (International Journal of Food Microbiology, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Seed priming with rutin enhances tomato resistance against the whitefly Bemisia tabaci - Juan Tang; Haowei Shen; Rong Zhang; Fengbo Yang; Jinyu Hu; Jinting Che; Hongyan Dai; Hong Tong; Qingjun Wu; Youjun Zhang; Qi Su (Pesticide Biochemistry and Physiology, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Rare earth elements detoxification mechanism in the hyperaccumulator Dicranopteris linearis: [silicon-pectin] matrix fixation - Hong-Xiang Zheng; Yu-Lu Yang; Wen-Shen Liu; Ying Zhong; Yue Cao; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Martin J. Hodson; Ye-Tao Tang (Journal of Hazardous Materials, 2023)

The application of 3D printing technology on starch-based product: A review - Liyuan Rong; Xianxiang Chen; Mingyue Shen; Jun Yang; Xin Qi; Yulin Li; Jianhua Xie (Trends in Food Science & Technology, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Trends in drought and effects on carbon sequestration over the Chinese mainland - Yang Li; Mengdi Li; Zhicheng Zheng; Wei Shen; Yanan Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Motor Circuit and Superior Temporal Sulcus Activities Linked to Individual Differences in Multisensory Speech Perception - Liyuan Li; Rong Li; Xinju Huang; Fei Shen; Hongyu Wang; Xuyang Wang; Chijun Deng; Chong Wang; Jiale Yang; Leiyao Zhang; Jiyi Li; Ting Zou; et al. (Brain Topography, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Complete genome sequence of Mycobacterium Mya-zh01, an endophytic bacterium, promotes plant growth and seed germination isolated from flower stalk of Doritaenopsis - Lijing Pan; Jimin Chen; Shumei Ren; Hanguo Shen; Biao Rong; Wen Liu; Zhenming Yang (Archives of Microbiology, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Farm animals and aquaculture: significant reservoirs of mobile colistin resistance genes - Yingbo Shen; Rong Zhang; Stefan Schwarz; Congming Wu; Jianzhong Shen; Timothy R. Walsh; Yang Wang (Environmental Microbiology, 2020)
Summary Colistin resistance has attracted substantial attention after colistin was considered as a last‐resort drug for the treatment of infections caused by carbapenem‐resistant and/or multidrug‐resistant (MDR) Gram‐negative bacteria in clinical settings. However, with the discovery of highly mobile colistin resistance ( mcr ) genes, colistin resistance has become an increasingly urgent issue worldwide. Despite many reviews, which summarized the prevalence, mechanisms, and structures of these genes in bacteria of human and animal origin, studies on the prevalence of mobile colistin resistance genes in aquaculture and their transmission between animals and humans remain scarce. Herein, we review recent reports on the prevalence of colistin resistance genes in animals, especially wildlife and aquaculture, and their possibility of transmission to humans via the food chain. This review also gives some insights into the routine surveillance, changing policy and replacement of polymyxins by polymyxin derivatives, molecular inhibitors, and traditional Chinese medicine to tackle colistin resistance.

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Network parameters quantify loss of assemblage structure in human‐impacted lake ecosystems - Rong Wang; John A. Dearing; C. Patrick Doncaster; Xiangdong Yang; Enlou Zhang; Peter G. Langdon; Hui Yang; Xuhui Dong; Zhujun Hu; Min Xu; Yanjie Zhao; Ji Shen (Global Change Biology, 2019)
Lake biodiversity is an incomplete indicator of exogenous forcing insofar as it ignores underlying deformations of community structure. Here, we seek a proxy for deformation in a network of diatom assemblages comprising 452 species in 273 lakes across China. We test predictions from network theory that nodes of similar type will tend to self‐organize in an unstressed system to a positively skewed frequency distribution of nodal degree. The empirical data reveal shifts in the frequency distributions of species associations across regions, from positive skew in lakes in west China with a history of low human impacts, to predominantly negative skew amongst lakes in highly disturbed regions in east China. Skew values relate strongly to nutrient loading from agricultural activity and urbanization, as measured by total phosphorus in lake water. Reconstructions through time show that positive skew reduces with temporal intensification of human impacts in the lake and surrounding catchments, and rises as lakes recover from disturbance. Our study illustrates how network parameters can track the loss of aquatic assemblage structure in lakes associated with human pressures.

Pre-colonization of PGPR triggers rhizosphere microbiota succession associated with crop yield enhancement - Yang Zhang; Xu Gao; Zongzhuan Shen; Chengzhi Zhu; Zixuan Jiao; Rong Li; Qirong Shen (Plant and Soil, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Linking soil N2O emissions with soil microbial community abundance and structure related to nitrogen cycle in two acid forest soils - Hongling Qin; Xiaoyi Xing; Yafang Tang; Haijun Hou; Jie Yang; Rong Shen; Wenzhao Zhang; Yi Liu; Wenxue Wei (Plant and Soil, 2019)

Application of Bacillus velezensis NJAU-Z9 Enhanced Plant Growth Associated with Efficient Rhizospheric Colonization Monitored by qPCR with Primers Designed from the Whole Genome Sequence - Yang Zhang; Xu Gao; Shuai Wang; Chengzhi Zhu; Rong Li; Qirong Shen (Current Microbiology, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Cadmium Accumulation Kinetics in Rhodococcus jostii RHA1 and Potential Effects of Brominated Flame Retardants - Shen Xu; Zhong-Bo Wei; Lian-Hong Wang; Rong Ji; Liu-Yan Yang; Ai-Jun Miao (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Combination of miR-21 with Circulating Tumor Cells Markers Improve Diagnostic Specificity of Metastatic Breast Cancer - Xingwang Yang; Xiaoming Wang; Hongyan Shen; Rong Deng; Kecheng Xue (Cell Biochemistry and Biophysics, 2015)

(2R,3S)-Pinobanksin-3-cinnamate improves cognition and reduces oxidative stress in rats with vascular dementia - Hong Liu; Min Zhao; Shen Yang; Dian-Rong Gong; De-Zhe Chen; De-Yong Du (Journal of Natural Medicines, 2015)

Hypocalcemia: a reversible cause of T wave alternans and heart failure - Yi-chen Yang; Fa-rong Shen; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2014)

Gorham-Stout syndrome in mainland China: a case series of 67 patients and review of the literature - Po Hu; Xiang-gui Yuan; Xin-yang Hu; Fa-rong Shen; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

Rhesus Monkey TRIM5α Has Distinct HIV-1 Restriction Activity Among Different Mammalian Cell Lines - Jian Gong; Xi-Hui Shen; Hui Qiu; Chao Chen; Rong-Ge Yang (Current Microbiology, 2011)

Rhesus monkey TRIM5α represses HIV-1 LTR promoter activity by negatively regulating TAK1/TAB1/TAB2/TAB3-complex-mediated NF-κB activation - Jian Gong; Xi-Hui Shen; Hui Qiu; Chao Chen; Rong-Ge Yang (Archives of Virology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Validation and dissection of quantitative trait loci for leaf traits in interval RM4923-RM402 on the short arm of rice chromosome 6 - BO SHEN; WEI-DONG YU; JING-HONG DU; YE-YANG FAN; JI-RONG WU; JIE-YUN ZHUANG (Journal of Genetics, 2011)

Fate of 15N after combined application of rabbit manure and inorganic N fertilizers in a rice–wheat rotation system - Cheng-Long Wu; Qi-Rong Shen; Jing-Dong Mao; Yang-Chun Xu (Biology and Fertility of Soils, 2010)

Mass spectrometric analysis reveals a functionally important PKA phosphorylation site in a Kir3 channel subunit - Radda Rusinova; Yu-Ming Albert Shen; Georgia Dolios; Julio Padovan; Heyi Yang; Madeleine Kirchberger; Rong Wang; Diomedes E. Logothetis (Pflügers Archiv - European Journal of Physiology, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Responses of Fusarium oxysporum f. sp. niveum to exogenously added sinapic acid in vitro - Hong-sheng Wu; Yang Wang; Wei Bao; Dong-yang Liu; Waseem Raza; Qi-wei Huang; Ze-sheng Mao; Qi-rong Shen (Biology and Fertility of Soils, 2009)

Effects of different nitrogen forms on the growth and cytokinin content in xylem sap of tomato (Lycopersicon esculentum Mill.) seedlings - Ying Lin Lu; Yang Chun Xu; Qi Rong Shen; Cai Xia Dong (Plant and Soil, 2009)

Allelopathic impact of artificially applied coumarin on Fusarium oxysporum f.sp. niveum - Hong-Sheng Wu; Waseem Raza; Dong-Yang Liu; Cheng-Long Wu; Ze-Shen Mao; Yang-Chun Xu; Qi-Rong Shen (World Journal of Microbiology and Biotechnology, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Identification and characterization of ten polymorphic microsatellite loci in the red panda Ailurus fulgens - Liang Zhang; Xu Liang; Zhihe Zhang; Fujun Shen; Wenping Zhang; Kun Wei; Zhi Yang; Rong Hou; Bisong Yue; Hiroshi Kamata; Ken Okabayashi; Shigeo Ohba; et al. (Conservation Genetics, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Comparison of (−)-Epigallocatechin-3-Gallate Elicited Liver and Small Intestine Gene Expression Profiles Between C57BL/6J Mice and C57BL/6J/Nrf2 (−/−) Mice - Guoxiang Shen; Changjiang Xu; Rong Hu; Mohit R. Jain; Sujit Nair; Wen Lin; Chung S. Yang; Jefferson Y. Chan; A.-N. Tony Kong (Pharmaceutical Research, 2005)

Upper Permian coral reef and colonial rugose corals in northwest Hunan, South China - Shen Jian-wei; Toshio Kawamura; Yang Wan-rong (Facies, 1998)